Green Market Development through Collaborations of Producers and Consumers: A Case of Kamalasai Green Market Network, Kamalasai District, Kalasin Province - Kahaban, Nittaya; Lanumtieng, Araya; Buddaduang , Arthit (JOURNAL OF SOUTHERN TECHNOLOGY, 2021)
In the past, the development of the green market faced a problem of not having systematic production plans. Consumers don't trust the products and lack appropriate market management models. This research aims to study 1) the situation and conditions of producers and consumers, production, behaviors, attitudes, and knowledge about green market development, 2) factors contributing to the participation of producers and consumers in the green market, and 3) to develop a green market model as a result of collaborations among the participants involved. The research sample consists of 16 manufacturers and 100 consumer representatives. This study employs participatory action research methods. Data were collected through focus group interviews, questionnaires implemented to manufacturer and consumers, production record form, participant and non-participatory observation and secondary data. Results show that the manufacturers had manufacturing skills but lacked marketing skills which are important for manufacturers to created different selling channels, developing their credibility, make known to consumers. It is also found that factors contributing to the return of customers to the green market are word-of-mouth communication and their trust in the manufacturers. It is also revealed that factors affect the decision to purchase non-toxic products are products, price, place and promotion. In addition, there are 5 factors that contribute to the participation of producers and consumers namely: closeness and awareness of common problems, expectations of mutual benefits, policies and local authorities, joint management and creation of constant learning processes. The development of the green market model from the participation of producers and consumers must follow 6 steps. These include creation of a solid manufacturing basis, engagement between producers and consumers, systematic marketing management, quality inspection, communication and public relations, and network expansion. Recommendations for the market development include integrating a collaborative plan, understanding community contexts and network. All these will lead to the process of developing green market in a concrete way.